Pharmacologic treatment for postviral olfactory dysfunction: a systematic review. Issue 7 (16th February 2016) - Harless, Lucas; Liang, Jonathan
Abstract : Background: Postviral olfactory dysfunction (PVOD) is the most common cause of olfactory dysfunction. Several treatments have been presented in the literature. The objective of this study is to systematically review the existing literature on the effectiveness of pharmacologic treatments for PVOD. Methods: We performed a literature search of PubMed, Ovid, and ScienceDirect from 1966 to 2014. Inclusion criteria included English‐language articles containing original data on pharmacologic treatment of PVOD with ≥5 subjects, measurable outcomes, and readily available treatments. Data was collected regarding study design, subject demographic information, clinical outcomes, and level of evidence. Two investigators reviewed all articles independently. Results: Of 445 abstracts identified, 8 articles were included, yielding 563 patients. Treatments investigated included oral corticosteroids, local injections of corticosteroids, zinc sulfate, alpha lipoic acid, caroverine, vitamin A, Ginkgo biloba, and minocycline. Outcome measures were determined by symptom scores and objective olfactory test methods—the most common being Sniffin' Sticks. Improvement was noted in subjects receiving oral corticosteroid therapy, local injections of corticosteroid, alpha lipoic acid, and caroverine, whereas vitamin A, zinc sulfate, Ginkgo biloba, and minocycline groups did not show significant improvement. Conclusion: The majority of therapies investigated that show benefit in treating PVOD are of poor quality. Although caroverine therapy showed benefit and is a level 1b study, etiologies of olfactory dysfunction other than PVOD were included as well, which clouds the results. Overall, there is no strong evidence for any pharmacologic treatment of PVOD in the literature.